BRIGHTNESS PERFORMANCE OF OFFICE INTERIOR DUE TO ROOM’S WINDOW COMPONENTS CONFIGURATION - Asri Dinapradipta; Johanes Krisdianto (Dimensi: Journal of Architecture and Built Environment, 2017)
The paper reports room’s brightness performance of glass dominance office building facade in Jakarta due to the use of tinted and reflective type of glass wall and the combination of these with internal roller and venetian shading types. Method used to collect the data was mainly by direct measurements at three open-plan office buildings with different window components configurations under overcast sky condition, and at parallel sitting positions. Comparing the results of measurement with the standard of luminance value for office building was used as data analysis. Results show that the window components configuration influenced the luminance values of the interior and thus affected mostly on the brightness perception of the rooms. Both tinted and reflective glazing configured with roller blinds yielded accepted luminance value of rooms’ surfaces. They contributed to bright enough light perception of the rooms. On the other hand, the problem of room’s luminance values may occur with the use of reflective type of glass configured with the venetian blinds. The blinds exacerbated the daylight coming from window in which it resulted in significantly high average luminance value of the window.